LITERASI DIGITAL PEREMPUAN PADA ORGANISASI PERSATUAN ISTRI PRAJURIT (PERSIT) - Erika, Desy (Master of Communication Science Program, Universitas Diponegoro, 2019)
Digital literacy of a woman is still a crucial problem, particularly on the social media. Many articles indicate that a woman as a potential audience target of consumption and contribution of information hoax. The goal of this research is to identifying of the affectivities of woman digital literacy on using digital media primarily on social media. Subject of the research is the Indonesian Army’s wives Association (PERSIT) Skadron 31 PUSPENERBAD Semarang. The method that is used in this case is qualitative method to observing and sharpening of information and analysis among resource discoveries. Result of research indicates that the wives of army mostly using social media in gaining information by using social media of gaining information by the way of accessing it with mobile-phone. Respondents use social media to exchanging information, preserving friendship relation, purchasing and marketing on-line, vacation and self-actualization. Socialization and warning are forwarding routinely during the meeting of the association. Regarding digital literacy it gives positive side and the women understand the negative side as well and its consequences of using digital media which is not appropriate, even the impact is not to those concerned but the family and the institution as well. At the PERSIT organization it is still strongly military hierarchy culture such as reprimand from the superior which gives repentance impact to the members that have been proven of misusing the digital media.